Tourism trends among Generation Y in Poland - Kowalczyk-Anioł, Joanna (Turyzm/Tourism, 2013)
On the basis of empirical studies and available sources, the author presents tourism as undertaken by young Poles from Generation Y, with reference to demographic, and above all generational changes. She focuses on presenting tourism preferences and typical behaviour. The analysis shows that their behaviour is similar to those observed by Generation Y globally. The similarities are also visible in tourism - new, post-modernist trends, such as gap year and internet couch surfing portals, as forms of independent travel organization, are becoming more and more popular. On the other hand, the consumptionist habits of Generation Y (preferences for comfort and entertainment), as well as an orientation towards family and friends, frequently travelling companions, can also be observed.